Physiological upper limits of left ventricular dimensions in highly trained junior tennis players - Basavarajaiah, S.; Wilson, M.; Naghavi, R.; Whyte, G.; Turner, M.; Sharma, S. (British Journal of Sports Medicine, 2007)
Background: The differentiation between physiological cardiac enlargement and cardiomyopathy is crucial, considering that most young non-traumatic deaths in sport are due to cardiomyopathy. Currently, there are few data relating to cardiac dimensions in junior elite tennis players. The aim of this study was to define the upper limits of left ventricular dimensions in a large cohort of national adolescent tennis players.